Sodium hypochlorite pentahydrate (NaOCl·5H2O) crystals; An effective re-oxidant for TEMPO oxidation. Issue 22 (2nd June 2016) - Okada, Tomohide; Asawa, Tomotake; Sugiyama, Yukihiro; Iwai, Toshiaki; Kirihara, Masayuki; Kimura, Yoshikazu
Abstract: The novel oxidant of sodium hypochlorite pentahydrate (NaOCl·5H2 O), which is now available for industrial and laboratory use has several advantageous properties. The crystalline material has 44% of NaOCl, contains minimal sodium hydroxide and sodium chloride, and the aqueous solution indicates pH 11–12. Herein, NaOCl·5H2 O crystals are examined for use as an oxidant for primary and secondary alcohols, with or without nitroxyl radicals, in the presence or absence of phase-transfer catalysts. The pentahydrate crystals alone (without nitroxyl radicals) demonstrate a powerful oxidizing ability, converting secondary alcohols to the corresponding ketones. In the presence of TEMPO (2, 2, 6, 6-tetramethylpiperidine 1-oxyl) or 1-Me-AZADO (1-methyl-2-azaadamantane N -oxy radical), sterically hindered secondary alcohols are oxidized without pH adjustment. A proposed mechanism for the oxidation is discussed. Graphical abstract: